Comparison of Bolster Versus Quilting Techniques on Outcome of Graft Take for Free Fibula Donor Site - Sehar, Nida; Arif, Fizzah; Ur Rahman, Mohammad Fazl; Shaikh, Safdar Ali (Biological and Clinical Sciences Research Journal, 2025)
Donor site management following free fibula flap harvest is crucial to optimize healing and minimize morbidity. While bolstering and quilting are both commonly employed to enhance graft adherence, their relative efficacy in donor site graft take and complication rates remains uncertain, particularly in head and neck oncologic reconstruction. Objective: This study aims to directly compare the outcomes of quilt and bolster when applied specifically to the free fibula flap donor site, in regard to graft take. Methods: After the ethical approval from the institutional review board, this Single center, parallel, open labelled, randomized control trial was conducted at Plastic Surgery Department at Aga Khan University Hospital from 01/July/2024 to 31/dec/2024. Through non-probability consecutive sampling, 48 patients aged 18-70 years, both gender, who underwent free fibula flap for reconstruction of head and neck tumors at were included in this study. Patients with prior history of limb trauma, peripheral vascular disease, underwent free fibula for other illnesses, such as osteoradionecrosis or trauma or extremity tumors were excluded from the present study. Results: The average flap donor site defect size was 93.5 ± 27.7 cm² in the bolster group and 90.4 ± 23.8 cm² in the quilting group (p = 0.649). The majority of split-thickness skin grafts (STSGs) in both groups were harvested from the contralateral leg—92% in the bolster group and 100% in the quilting group—while only 8% of STSGs in the bolster group were taken from the same leg (p = 0.162). The mean percentage of graft take was 86.2% ± 5.9 in the bolster group and 85.8% ± 7.5 in the quilting group, showing no significant difference (p = 0.812). Donor site complications were observed in 13% of patients in each group (p = 0.98), indicating comparable complication rates between the two techniques. Conclusion: Both bolstering and quilting techniques yield comparable outcomes in terms of graft take and complication rates at the free fibula donor site.